Effect of transcranial magnetic stimulation combined with transcutaneous auricular vagus nerve stimulation on mild cognitive impairment: a study protocol for a randomized controlled trial - Zhang, Jingjing; Ma, Jun; Rao, Yao; Wu, Jiali; Xu, Hui; Ni, Jiawei; Zhao, Zhiwei; Wang, Cong; Shan, Chunlei (Frontiers in Aging Neuroscience, 2025)
BackgroundNon-invasive brain stimulation techniques have been widely used in patients with mild cognitive impairment (MCI) to accelerate the recovery of their cognitive functions. However, the clinical efficacy of single non-invasive stimulation techniques in treating MCI still requires further improvement. The combination of two non-invasive neuromodulation techniques can enhance the synergistic effects of the treatment. Repetitive transcranial magnetic stimulation (rTMS) regulates the cortical-subcortical network in a “top-down” manner, while transcutaneous auricular vagus nerve stimulation (taVNS) modulates the brainstem-limbic system-cortical pathway in a “bottom-up” fashion. We will combine rTMS and taVNS, anticipating synergistic regulation through dual pathways to achieve multi-level neural remodeling effects and improve MCI.MethodsThis study will investigate the effectiveness of combined rTMS and taVNS therapy in improving the cognitive function of MCI patients. We will enroll 88 participants and randomly assign them to single-stimulation groups and combined-stimulation groups. The single-stimulation groups will be further randomized in a 1:1 ratio into a rTMS + sham taVNS stimulation group and a taVNS + sham rTMS stimulation group; the combined-stimulation groups will be randomized in a 1:1 ratio into an rTMS + taVNS group and an rTMS sham stimulation + taVNS sham stimulation group. All patients will receive treatment for 4 weeks. Assessments will be conducted before treatment (T0), 4-week treatment (T1), and 4-week post-treatment follow-up (T2). The primary outcome measure will be the Chinese version of the Montreal Cognitive Assessment Basic (MoCA-B), while secondary outcome measures will include the Rivermead Behaviour Memory Test (RBMT), the modified Barthel Index (MBI) for activities of daily living, and the latency and amplitude of event-related potential (ERP) P300.DiscussionThis study is a clinical randomized controlled trial, which innovatively combines two non-invasive modulation techniques to improve cognitive function in patients with MCI. This study can validate the clinical efficacy of the combined TMS + taVNS stimulation, providing a theoretical basis for the application of this technology in clinical settings.